Burden of serious fungal infections in the Netherlands. Issue 6 (28th April 2020) - Buil, Jochem B.; Meijer, Eelco F. J.; Denning, David W.; Verweij, Paul E.; Meis, Jacques F.
Summary: Background: Fungal diseases have an ever‐increasing global disease burden, although regional estimates for specific fungal diseases are often unavailable or dispersed. Objectives: Here, we report the current annual burden of life‐threatening and debilitating fungal diseases in the Netherlands. Methods: The most recent available epidemiological data, reported incidence and prevalence of fungal diseases were used for calculations. Results: Overall, we estimate that the annual burden of serious invasive fungal infections in the Netherlands totals 3 185 patients, including extrapulmonary or disseminated cryptococcosis (n = 9), pneumocystis pneumonia (n = 740), invasive aspergillosis (n = 1 283), chronic pulmonary aspergillosis (n = 257), invasive Candida infections (n = 684), mucormycosis (n = 15) and Fusarium keratitis (n = 8). Adding the prevalence of recurrent vulvo‐vaginal candidiasis (n = 220 043), allergic bronchopulmonary aspergillosis (n = 13 568) and severe asthma with fungal sensitisation (n = 17 695), the total debilitating burden of fungal disease in the Netherlands is 254 491 patients yearly, approximately 1.5% of the country's population. Conclusion: We estimated the annual burden of serious fungal infections in the Netherlands at 1.5% of the population based on previously reported modelling of fungal rates for specific populations at risk. With emerging new risk groups and increasing reports on antifungal resistance, surveillance programmes are warranted to obtain more accurate estimates of fungal disease epidemiology and associated morbidity and mortality.